2020
DOI: 10.3390/su12052048
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Traffic Detector Layout Based on Complex Network Theory

Abstract: With the recent development of traffic networks, traffic detector layout has become very complicated, due to the complexity of traffic network structures and states. Thus, this paper presents an optimal method for traffic detector layout based on network centrality using complex network theory. It mainly depends on the topology of the traffic network, and does not depend on pre-conditions (e.g., OD (Origin Destination)) traffic, path traffic, prior matrix, and so on) or consider route-choosing behavior too muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…R zip = {(x, y)|(x, y) within the boundary of the zip code} (4) where (x, y) is a pair of latitude and longitude. Figure 4 shows an example of R epa and R zip .…”
Section: Traffic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…R zip = {(x, y)|(x, y) within the boundary of the zip code} (4) where (x, y) is a pair of latitude and longitude. Figure 4 shows an example of R epa and R zip .…”
Section: Traffic Variablesmentioning
confidence: 99%
“…The exposure to traffic-related emissions has led to concerns of potential adverse health effects for many years [1]. Motor vehicle traffic is seen as a leading cause of air quality contamination in many urban areas [2][3][4]. In particular, the traffic-related particulate pollution (e.g., PM 2.5 ) is reported to contribute up to 90% of air pollution in some cities in developing countries [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical examples demonstrated that the proposed deployment model could determine the optimal scheme of detectors. An et al [8] presented an optimal method for loop-detector layout based on network centrality. They built a traffic network centrality model (TNCM) that considers travel time and origin-destination (OD) demand.…”
Section: Introductionmentioning
confidence: 99%
“…is breakthrough made it possible to create networks with the best complexity [4]. An et al optimized the layout of traffic detectors using complex networks, which extended the practical application of complex networks in the field of transportation [5]. In addition, Karunakaran and Selvaganesh introduced the concept of neighborhood matrix.…”
Section: Introductionmentioning
confidence: 99%